Academic expectations among international students from North-Western China: A case of technology use during and post COVID-19 - AL-Qadri, Abdo Hasan; Ahmed, Salah A. M.; Suliman, Mohammed A. E.; Al-khresheh, Mohammad H.; Boudouaia, Azzeddine; Zhao, Wei; Zhang, Wenlan (Frontiers in Psychology, 2022)
This study examines the influence of the COVID-19 crisis on academic expectations among international students from north-western China. According to past studies, academic expectations are multifaceted, making it critical to test the methods employed to assess this fundamental trait. The outbreak of COVID-19 has resulted in various significant changes in education, which have shifted from traditional to online or mixed formats. As a result, examining international students' academic expectations along with their interactions with adopted technologies is a topic that addresses the current situation and issues. A mixed approach, comprising two different instruments (questionnaire and interview), was followed to achieve this primary objective. While a survey with a questionnaire was undertaken with 551 international students, divided into two groups, ten students were interviewed during and after the lockdowns. The findings revealed that COVID-19 had a significant impact on the academic expectations of students as well as many elements such as training for employment, personal and social development, international student mobility, motivation, social pressure, and social interaction with the help of supporting technologies. In terms of gender, men outperformed women in motivation, social interaction, training for employment, and personal and social development factors. Similarly, as per the grade variable (undergraduate, postgraduate, doctoral), the same higher trend was seen in postgraduates. Based on these findings, a set of recommendations was put forward. In the future, technology will be helpful in China's educational sector, such as online group collaboration, open education, managing student retention, and supervising teachers' recruitment.